Upaya Meningkatkan Hasil Belajar Pai Melalui Metode Demonstrasi pada Siswa Kelas II Sd Negeri 1 Campang Kecamatan Gisting Kabupaten Tanggamus Tp. 2015/2016 - Luviadi, Ahmad; Akmaluddin, Akmaluddin (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2016)
One indicator is the result of learning student has mastery of knowledge and development of skills or abilities required to use this knowledge, as shown by the fulfillment of the KKM. While that happened in class II SDN 1 Campang District of Gisting Tanggamus, the average value is still below the KKM. Among the success factors of the learning process is largely determined by the ability of teachers to select and use the method as a learning strategy appropriate to the circumstances and abilities of students so that learning outcomes in accordance with expectation. One of the methods of learning that can be applied in teaching PAI is a demonstration. By the demonstration method expected learners can understand and practice them directly.Specifically, the study to determine what the demonstration Methode can improve student learning outcomes? With the subject of research grade II SDN 1 Campang districts Gisting Tanggamus, factors that could affect, measures, and the advantages and disadvantages (weaknesses) method of demonstration. Knowing that all of it can be given some suggestions that can be a consideration for PAI teachers, particularly PAI in improving learning outcomes for students in the school.This study uses classroom action research (PTK) with a qualitative approach or naturalistic.Data aggregation by using observation, interview, documentation, and learning outcomes test. Whereas test results for data analysis using three way of activities, data reduction, display/presentation of data and verification/conclusion ,From the results of the study revealed that; using the method of demonstration can improve learning outcomes PAI in class II SDN 1 Campang districts Gisting Tanggamus district academic year 2015 / 2016.Is demonstrated matter student learning outcomes is increasing in every cycle.When the pre survey class average value of only 69, 59 with KKM 75. While the classroom action research conducted in the first cycle the average value rose to 74.9. and the second cycle the average value increased to 77,3 by percentage of completeness in the first cycle of 56% and the second cycle by 87%.